2020
DOI: 10.1111/mms.12773
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting trends in gray seal (Halichoerus grypus) pup production throughout the increasing northwest Atlantic metapopulation

Abstract: The northwest Atlantic subspecies of gray seal (Halicheorus grypus grypus) has been increasing for more than a half century and has reestablished breeding colonies in Canadian and US waters. In 2016, visual, oblique, and vertical large-format digital photographic surveys were conducted at all known breeding colonies in the northwest Atlantic. Total pup production in the northwest Atlantic was estimated to be 109,000 (SE = 17,500) pups. At 87,500 (SE = 15,100) pups, Sable Island accounts for 80% of total pup pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Our conceptual model does not differentiate between males and females the same, so we have estimated peak haul out as the average of time hauled out for males and females. Notably the timing of the peak haul out from satellite telemetry on the island in mid-January is consistent with birth distribution models (Bowen et al, 2007;den Heyer et al, 2020), estimates of mean pup birthdate from individually marked adults (Bowen et al, 2020), and the reproductive biology of the seals. The model 205 is built around three hypotheses:…”
Section: 4supporting
confidence: 77%
See 1 more Smart Citation
“…Our conceptual model does not differentiate between males and females the same, so we have estimated peak haul out as the average of time hauled out for males and females. Notably the timing of the peak haul out from satellite telemetry on the island in mid-January is consistent with birth distribution models (Bowen et al, 2007;den Heyer et al, 2020), estimates of mean pup birthdate from individually marked adults (Bowen et al, 2020), and the reproductive biology of the seals. The model 205 is built around three hypotheses:…”
Section: 4supporting
confidence: 77%
“…Another remarkable phenomena is the winter increase in chl-a standing stocks in the leeward region of SI (SOM5) that is consistent with the increase of seal population on SI over the last 20 years. From the late 1990's to the late 2010's the population has continuously increased at a rate of about 5-7% per year (Figure 6 den Heyer et al, 2020). We demonstrated that the average chl-a increased within the plume southward of Sable Island at a faster rate than the surrounding control boxes in winter.…”
Section: 23mentioning
confidence: 64%
“…The copyright holder for this preprint (which this version posted July 12, 2021. ; https://doi.org/10.1101/2021.07.10.451928 doi: bioRxiv preprint 2021). Sable Island supports the largest breeding colony of grey seals in the world with an estimated 87,500 pups (SE = 15,100) born on the island in 2016, comprising 80% of the total grey seal pup production in the Northwest Atlantic (den Heyer et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The Sable Island grey seal breeding colony has increased dramatically over the past half century with near maximum population growth of 13% per year between the 1960s and late 1990s (Bowen 2011) and a reduced rate of increase of 4% from 1997 to 2016 (den , den Heyer et al 2021. Female grey seals born during a period of exponential population growth in the 1980s and 1990s had apparent juvenile survival probabilities to reproductive recruitment of 0.7-0.8 (den Heyer et al 2013).…”
Section: Implications For Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation